Impacts of Interannual Variations of Chlorophyll on Seasonal Predictions of the Tropical Pacific - Doi, Takeshi; Behera, Swadhin (Frontiers in Climate, 2022)
In this study, we explored impacts of interannual variations of chlorophyll on seasonal predictions of the tropical Pacific by the SINTEX-F2 dynamical climate prediction system, which is highly skillful at predicting El Niño/Southern Oscillation (ENSO) and other tropical climate phenomena. We conducted twin re-forecast experiments; one system used the observed climatology of chlorophyll to compute the shortwave absorption in the upper ocean, while the other used the observed chlorophyll with year-to-year variations. Although the chlorophyll impacts on predictions of the Niño 3.4 index were limited, improvements are noticed in the predictions of sea surface temperature over the eastern edge of the Western Pacific Warm Pool. This region corresponds to the separation between warm, low-salinity waters of the warm Pool and cold, high-salinity upwelled waters of the Pacific cold tongue in the central-eastern equatorial Pacific. The improvement was very striking in the 2015 case, when a super El Nino occurred.